2022
DOI: 10.1088/1752-7163/ac5d8c
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical detection dogs for the identification of SARS-CoV-2 infections from axillary sweat and breath samples **

Abstract: A PCR test of a nasal swab is still the “gold standard” for detecting a SARS-CoV-2 infection. However, PCR testing could be usefully complemented by non-invasive, fast, reliable, cheap methods for detecting infected individuals in busy areas (e.g. airports and railway stations) or remote areas. Detection of the volatile, semivolatile and non-volatile compound signature of SARS-CoV-2 infection by trained sniffer dogs might meet these requirements. Previous studies have shown that well-trained dogs can detect SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 52 publications
0
31
0
1
Order By: Relevance
“…Indeed, a varying collection period was applied depending on the body region across the reviewed COVID-19-detection studies. While a short swabbing of the crook of the arm, wrist, face or neck was sufficient for high diagnostic accuracies with sensitivities and specificities above 91% in three studies (69,70,134), studies that used axillary sweat or other sweat type chose a longer collection period of around 1-20 min (51,117,(184)(185)(186)(187)(188)(189)(190)(191)(192) or even periods of hours in case of clothes (47, 144). However, in most cases these periods were arbitrarily chosen (4).…”
Section: Sweat and Body Odormentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a varying collection period was applied depending on the body region across the reviewed COVID-19-detection studies. While a short swabbing of the crook of the arm, wrist, face or neck was sufficient for high diagnostic accuracies with sensitivities and specificities above 91% in three studies (69,70,134), studies that used axillary sweat or other sweat type chose a longer collection period of around 1-20 min (51,117,(184)(185)(186)(187)(188)(189)(190)(191)(192) or even periods of hours in case of clothes (47, 144). However, in most cases these periods were arbitrarily chosen (4).…”
Section: Sweat and Body Odormentioning
confidence: 99%
“…For example, Gokool et al provided preliminary evidence that the specific odor persists for months in worn cotton shirts ( 193 ). Sweat samples for COVID-19-detection were stored cooled or at room temperature for around 2 h ( 194 ), 24–72 h ( 70 , 185 187 , 189 , 190 , 192 ), 1 week ( 188 ), or even up to 6 months in triple zip-lock plastic bags ( 69 ) before being presented to a dog. In some studies, sweat samples (and clothes) were frozen and then presented to the dogs thawed after longer storage periods in order to preserve VOCs ( 47 , 52 , 117 , 134 , 191 ).…”
Section: Samples For Use In Training and Testingmentioning
confidence: 99%
“…Several studies have shown the ability of medical scent detection dogs to identify samples from SARS-CoV-2 infected individuals with high accuracy, highlighting the role such dogs could play in the management of a pandemic 1–13. Previous research showed that different body fluids, such as saliva, sweat and urine and other sample types like worn face masks are suitable for detection, which suggests that there is a general SARS-CoV-2 infection associated odour that dogs can be trained on 14–16. In addition, our group demonstrated that such dogs were able to differentiate SARS-CoV-2 infection from other acute viral respiratory tract infections 17.…”
Section: Introductionmentioning
confidence: 60%
“…BMJ Global Health which suggests that there is a general SARS-CoV-2 infection associated odour that dogs can be trained on. [14][15][16] In addition, our group demonstrated that such dogs were able to differentiate SARS-CoV-2 infection from other acute viral respiratory tract infections. 17 However, most of the current data were generated in laboratory settings, rather than in a real-world scenario or lacked the verification of SARS-CoV-2 infections by a PoC-antigen test and real-time quantitative reverse transcription-PCR (RT-qPCR).…”
Section: How This Study Might Affect Research Practice or Policymentioning
confidence: 82%
See 1 more Smart Citation